Reusing model components in logistics simulation and device emulation in container terminal operation with open-source framework DESMO-J. (1st January 2012) - Joschko, Philip; Page, Bernd; Brandt, Christopher
With this applied research study, we are demonstrating how an open-source Java simulation framework can be extended beyond standard logistic studies as the main application domain so far to evaluate and test container terminal control systems. We are investigating whether implementing model components of container terminals in such a flexible way that they can be applied in logistics simulation as well as in device emulation test beds is feasible. This paper outlines our experience in extending DESMO-J for a broader range of applications in the context of container terminals and in developing reusable model components for simulation and emulation.